Asbestos in commercial indian talc. Issue 5 (27th March 2019) - Fitzgerald, Sean; Harty, Elizabeth; Joshi, Tushar Kant; Frank, Arthur L.
Abstract: Background: Easily available commercial Indian talc products widely used in Southeast Asia were examined for the presence of asbestos. Asbestos in talc products carry all risks of asbestos‐related disease. Methods: Using polarizing light microscopy, transmission electron microscopy (TEM), electron diffraction, and X‐ray analysis, multiple over‐the‐counter Indian talc products were examined for the presence of asbestos. Results: Results In an initial group of five Indian talc products, one was found to contain tremolite asbestos. The second group of eight products was tested and six of eight contained tremolite asbestos as well. No other regulated amphibole was found. Conclusion: Large quantities of body talc products containing asbestos are used throughout Southeast Asia and are likely to pose a public health risk for asbestos‐related diseases, especially for the cancers related to asbestos exposure. The country of origin in which the talc examined was sourced for production is unknown to the authors, and further investigation to measure associated public health risk is needed.